2022-VA-182-ESGO May transvaginal natural orifice transluminal endoscopic surgery VNOTES sentinel lymph node biopsy be the future of endometrial cancer surgery?. (20th October 2022) - Comba, Cihan; Demirayak, Gokhan; Karakaş, Sema; Aykut Ozdemir, Isa
Abstract : Introduction/Background: Transvaginal natural orifice transluminal endoscopic surgery (VNOTES) is being used with increasing frequency in gynecology and has advantages such as quick return to normal life and less pain. The sentinel lymph node concept has been accepted in recent guidelines in endometrial cancer. We have shown this approach can be applicable for sentinel lymph node dissection in patients with endometrial cancer. Methodology: We will show step by step video demonstration. 1. to make incision to vagina 2. injection of ICG 2. to install trans vaginal access platform 3. to develop retroperitoneal space 4. detection of the sentinel lymph node 5. Removal of the sentinel lymph node 6. vNOTES hysterectomy 7. Closure of the incisions Results: The approach has performed for three patients with endometrial cancer until today. No complication was detected. All of them discharged postoperative day 1. Blood loss were under 50 ml. One of these patients was at stage IIIC1 treated with chemoradiotherapy, and the other two were at stage IA endometrioid type were under observation. No recurrence was found. Conclusion: VNOTES sentinel lymph node dissection may be an alternative approach of treatment for patients with endometrial cancer.